Nanotoxicology in Safety Assessment of Nanomaterials: Book Presentation - Louro, Henriqueta (2022)
Presentation of the book 'Nanotoxicology in Safety Assessment of Nanomaterials' (https://link.springer.com/book/10.1007/978-3-030-88071-2): Worldwide experts present the latest knowledge on nanotoxicology Innovative approaches in synthesis/application of nanomaterials Provides central knowledge for applying safe and sustainable nanotechnologies with a safe-by-design” approach